Tetrasubstituted cyclopentadienones as suitable enantiopure ligands with axial chirality. Issue 41 (21st September 2017) - Prati, L.; Mancinelli, M.; Ciogli, A.; Mazzanti, A.
Abstract : A series of thermally stable atropisomeric phencyclones has been successfully synthesized as ligands in new ruthenium-based enantioselective hydrogenation catalysts. Abstract : A series of thermally stable atropisomeric phencyclone ligands (Δ G ‡rac > 35 kcal mol −1 ), bearing two chiral axes, has been successfully synthesized, taking into account the results of DFT calculations on model systems. The absolute configurations of the novel atropisomers have been assigned using TD-DFT simulation of ECD spectra. Atropisomeric phencyclones herein presented pave the way towards new ruthenium-based enantioselective hydrogenation catalysts.